Establishment Of A Voluntary Self Regulation Non-Governmental Consumer Dispute Resolution Organization In Principle Of Fairness And Equality - Satrio Ageng Rihardi; Budi Santoso; Ery Agus Priyono (Universitas Negeri Semarang, 2025)
Developments in the economic sector will increase the production and consumption power of society. If consumers suffer losses, economic agents are obliged to be able to provide compensation for the products sold to consumers. The UUPK provides for alternative dispute resolution outside the judicial system, namely through the Non-Governmental Consumer Protection Agency (LPKSM). Settlement of consumer disputes in LPKSM with a voluntary self-regulation mechanism or self-regulation as an effort to regulate, control, evaluate, select and determine a performance that will certainly minimise or reduce the number of disputes that go to the Consumer Disputes Board (BPSK) or the District Court. The research method uses normative legal research by tracing literature studies using a normative legal approach in order to obtain new perceptions of the situation by providing a new form of concept in resolving consumer disputes at LPKSM. The concept of the LPKSM's Voluntary Self-Regulation Mechanism is designed to help various parties, especially business actors and consumers, quickly and inexpensively to resolve disputes at the lowest level before they reach the BPSK or the courts. As a form of voluntary self-regulation, mediation is the right method to implement the principle of equality before the law. The LPKSM acts as a third party, an outsider who is declared to be neutral (impartial) and who helps the parties to come to an agreement. The benefits of resolving consumer disputes are quick, inexpensive and confidential, and can even be described as a win-win solution, set out in a joint peace deed.